Creative dramatics a technique in teaching social studies to the educable mentally retarded (intermediate level) - Mendoza, Evelina Maducdoc 1944- (1973)
The purpose of the study was to present the possible use of creative dramatics as a technique in the teaching of social studies for the educable mentally retarded, intermediate level. Library research was used in the study in an attempt to discuss the topics: social characteristics of the educable mentally retarded, importance of social studies in the curriculum, values of creative dramatics, stages in its development, examples of situations in the social studies, and an evaluation guide for the use of the teacher. The researcher found out that this technique may improve language, manner of expression, increased auditory memory, personal achievement, independence and social interaction.